Path Analysis for Investigating the Main Factors Behind Chronic Kidney Disease - Azhy Akram Aziz; Aras Jalal Mhamad; Renas Abubaker Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
Kidney failure is a global public health problem, with increasing incidence and prevalence, high costs, and poor outcomes, there is even a substantially higher prevalence of the earlier stages of chronic kidney disease (CKD), with adverse outcomes, including loss of kidney function. Strategies to improve outcomes will require a global effort directed at the earlier stages of CKD. The study's goal is to look at the relationship between factors that causes kidney failure based on creatinine and urea. Data were collected from Delvin pathological laboratory The path analysis method results reveal is underlying mechanism through which statistical tools, as relationship between factors; phosphorus, phosphates, albumin, calcium, glucose, and patient’s age, creatinine and urea, which are caused kidney failure issue. The results show arrangement about factors effectiveness and the effects of phosphorus, phosphates, albumin, calcium, glucose, and patient’s age are statistically significant as mentioned at section five of the study. This gives the conclusion that kidney failure problem must be more concern.